Abnormalities in serum biomarkers correlate with lower cardiac index in the Fontan population. (5th July 2016) - Marino, Bradley S.; Goldberg, David J.; Dorfman, Adam L.; King, Eileen; Kalkwarf, Heidi; Zemel, Babette S.; Smith, Margaret; Pratt, Jesse; Fogel, Mark A.; Shillingford, Amanda J.; Deal, Barbara J.; John, Anitha S.; et al.
Abstract : Background: Fontan survivors have depressed cardiac index that worsens over time. Serum biomarker measurement is minimally invasive, rapid, widely available, and may be useful for serial monitoring. The purpose of this study was to identify biomarkers that correlate with lower cardiac index in Fontan patients. Methods and results: This study was a multi-centre case series assessing the correlations between biomarkers and cardiac magnetic resonance-derived cardiac index in Fontan patients ⩾6 years of age with biochemical and haematopoietic biomarkers obtained ±12 months from cardiac magnetic resonance. Medical history and biomarker values were obtained by chart review. Spearman's Rank correlation assessed associations between biomarker z-scores and cardiac index. Biomarkers with significant correlations had receiver operating characteristic curves and area under the curve estimated. In total, 97 cardiac magnetic resonances in 87 patients met inclusion criteria: median age at cardiac magnetic resonance was 15 (6–33) years. Significant correlations were found between cardiac index and total alkaline phosphatase (−0.26, p=0.04), estimated creatinine clearance (0.26, p=0.02), and mean corpuscular volume (−0.32, p<0.01). Area under the curve for the three individual biomarkers was 0.63–0.69. Area under the curve for the three-biomarker panel was 0.75. Comparison of cardiac index above and below the receiver operating characteristic curve-identified cut-off points revealed significant differences for each biomarker (p<0.01) and for the composite panel [median cardiac index for higher-risk group=2.17 L/minute/m 2 versus lower-risk group=2.96 L/minute/m 2, (p<0.01)]. Conclusions: Higher total alkaline phosphatase and mean corpuscular volume as well as lower estimated creatinine clearance identify Fontan patients with lower cardiac index. Using biomarkers to monitor haemodynamics and organ-specific effects warrants prospective investigation.